The Culture of Mee Bu for Declining Stunting: Aceh Local Wisdom in the Process of Reproduction - Tuti Marjan Fuadi (Universitas Syiah Kuala, 2018)
This study aims to find out the process of mee bu tujoh bulen as one of the cultures of the Acehnese community that seeks to meet the nutritional needs of pregnant and prevents stunting mothers. Qualitative research with a phenomenological approach is used to study the cultural phenomena of mee bu tujoh bulen from the views and experiences of the people. Respondents in this study were pregnant women, traditional birth attendants, traditional leaders and community leaders. Data processing is done by using data reduction analysis, data display, and conclusion drawing/verification techniques that are presented in narrative form. The results showed that the ingredients presented in mee bu culture consisted of bu kulah (rice wrapped using young banana leaves which had been steamed and then rice wrapped in pyramid shape), side dishes consisting of grilled fish, beef, roasted chicken, cooked duck curries, eggs, and various types of fruit. In addition to those ingredients, the in-laws also prepared a set of betel (completed with ingredients such as areca nut, gambier, lime, cloves and tobacco or called bakong in local language). To sum up, the food brought to mee Bu Tujoh Bulen in cultural ceremony by parents-in-law to pregnant daughter-in-law contains good nutrients to support the fulfillment of nutrition for pregnant women therefore it can prevent and reduce the prevalence of stunting children.